2017
DOI: 10.1038/nbt.3841
|View full text |Cite
|
Sign up to set email alerts
|

Elevating the conversation about GE crops

Abstract: Journal article; EditorialIFPRI3; ISIEPTDNon-P

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…In addition, although interviewed farmers could improve their knowledge, reduce their health risks and lower their dependency on external funding, the application of organic farming methods often resulted in a higher workload, especially for women. This confirms studies on organic farming in Karnataka, India (Patil et al, 2014), as well as in other parts of the world (Bachmann, 2012; Gould et al, 2016).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, although interviewed farmers could improve their knowledge, reduce their health risks and lower their dependency on external funding, the application of organic farming methods often resulted in a higher workload, especially for women. This confirms studies on organic farming in Karnataka, India (Patil et al, 2014), as well as in other parts of the world (Bachmann, 2012; Gould et al, 2016).…”
Section: Resultssupporting
confidence: 84%
“…Making compost, the preparation of liquid manure, treatment of seeds and preparing bio-pesticides are necessary farming practices in organic agriculture. These farming practices entail an increased workload for farmers, which has been confirmed in other regions of India (Eyhorn et al, 2007), as well as other countries (Bachmann, 2012; Gould et al, 2016). Nevertheless, many farmers indicated that avoiding expensive agrochemicals and the possibility of an independent supply of manure and bio-pesticide outweighed the higher workload.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Genetically engineered crops that produce insecticidal proteins from the bacterium Bacillus thuringiensis (Bt) have revolutionized pest control and were planted on over 100 million hectares worldwide in 2017 [1]. These transgenic Bt crops can suppress pests, reduce insecticide use, and increase farmer profits [2,3,4,5,6]. However, adaptation of insect pests to Bt toxins has reduced these benefits [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…To address the risk of insect resistance, IRM programs have been proactively implemented wherever Bt crops have been commercialized, with these programs being mandatory in some countries including the USA, Canada, Australia, the EU, the Philippines and South Africa (Matten et al, 2008). Central to these IRM programs is the concept of a “refuge,” which is an area of plants (typically of the crop of interest) that do not contain any Bt protein and thereby support the production of Bt-susceptible insects (Gould, 1998; Gould et al, 2016). Refuges represent a short-term cost to growers because they incur greater pest damage and require additional management, and thus refuge adoption by growers is generally much higher in countries where IRM is a regulatory requirement e.g., Australia, Canada and the US.…”
Section: Opportunities and Challenges For Using Bt Crops In Ipmmentioning
confidence: 99%